Shariah-Integrated Early Warning Framework for Financial Distress in Indonesian Islamic Banks - Windu Anggara; Saparuddin Siregar; Kamilah K (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Indonesia’s Islamic banking sector has grown rapidly, driven by Shariah-compliant operations, but faces vulnerabilities from complex governance and regulatory demands. Ensuring financial stability requires effective predictive tools tailored to these unique operational and regulatory conditions. This study aims to develop a structural Early Warning System (EWS) to predict financial distress in Islamic banks, integrating macroeconomic indicators, bank-specific performance variables, and a Shariah Compliance Index, with Islamic corporate governance and risk management as mediators. Data from 14 Islamic commercial banks over 2015–2024 were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results show that internal bank factors and Shariah compliance significantly strengthen governance and risk management, which in turn reduces financial distress, while macroeconomic variables have no direct effect. The findings highlight the central role of internal governance and compliance in resilience. The proposed framework provides a unified, Shariah-aligned predictive system, enabling regulators, Shariah Supervisory Boards, and bank executives to implement evidence-based strategies. This study also lays the groundwork for a Shariah-based Financial Distress Index, enhancing the sector’s ability to manage operational and regulatory complexities effectively.